2022
DOI: 10.2196/37278
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Stress Management Intervention for University Students in Indonesia (Rileks): Feasibility Study Using a Pretest-Posttest Design

Abstract: Background University students are susceptible to excessive stress. A web-based stress management intervention holds promise to improve stress but is still at a novel stage in Indonesia. Objective The aim of this paper was to report the feasibility of the intervention we developed—Rileks—among university students in Indonesia in terms of acceptability and usability, and to propose recommendations for future improvements. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…It is also in line with the development of digital penetration in Indonesia, which is said to reach >70% according to the Indonesian Internet Service Provider Association [11]. However, to date, only 1 randomized controlled trial using behavioral activation for depression [12] and 2 feasibility studies of cognitive and behavioral therapies for university students [12][13][14] have been conducted among Indonesian populations. Although these studies support the utility of internet-delivered mental health interventions in Indonesian populations, further studies are needed to explore other culturally appropriate therapy approaches.…”
Section: Introductionmentioning
confidence: 77%
“…It is also in line with the development of digital penetration in Indonesia, which is said to reach >70% according to the Indonesian Internet Service Provider Association [11]. However, to date, only 1 randomized controlled trial using behavioral activation for depression [12] and 2 feasibility studies of cognitive and behavioral therapies for university students [12][13][14] have been conducted among Indonesian populations. Although these studies support the utility of internet-delivered mental health interventions in Indonesian populations, further studies are needed to explore other culturally appropriate therapy approaches.…”
Section: Introductionmentioning
confidence: 77%
“…Positive user experience outcomes were associated with asynchronously-delivered interventions that provided motivational and encouraging written feedback (Cook et al, 2019;Karyotaki et al, 2022;Küchler et al, 2023) and personalized or individually tailored messages of support from mental health professionals (Hennemann et al, 2022;Peynenburg et al, 2022;Rice et al, 2020). Similar positive user experiences were linked to receiving timely written feedback, within 24 to 48 hours after module completion (Cook et al, 2019;Juniar et al, 2022;Karyotaki et al, 2022;Küchler et al, 2023;Wahlund, 2022) and automated weekly emails or texts with personalized recommendations (Stapinski et al, 2021). Furthermore, participants reported positive experiences when coaches regularly called to monitor their progress and used motivational interviewing to promote continued participation (Garnefski & Kraaij, 2023).…”
Section: Asynchronous Guided and Partially Guided Interventionsmentioning
confidence: 90%
“…The results of participants’ satisfaction, positive and negative outcomes, and effects showed the program’s feasibility and that participants were highly satisfied with it, indicating that they received the kind of support the program intended to provide [ 77 , 78 ]. Considering previous studies with dropout rates ranging from 7.2% to 44.2% [ 72 , 78 , 79 ], this study reported a low dropout rate of 20% (8/40).…”
Section: Discussionmentioning
confidence: 99%